The Latin American dimension in a political leadership’s construction: the Rosas by Jorge Gelman - Paz, Gustavo L. (Boletín del Instituto de Historia Argentina y Americana Dr. Emilio Ravignani, 2022)
Some thoughts on the works by Jorge Gelman on the political leader Juan Manuel de Rosas, and Julio Pinto’s essay on political leadership in the 19th Century.